2018
DOI: 10.1186/s13045-018-0678-1
|View full text |Cite
|
Sign up to set email alerts
|

Advances in multiple omics of natural-killer/T cell lymphoma

Abstract: Natural-killer/T cell lymphoma (NKTCL) represents the most common subtype of extranodal lymphoma with aggressive clinical behavior. Prevalent in Asians and South Americans, the pathogenesis of NKTCL remains to be fully elucidated. Using system biology techniques including genomics, transcriptomics, epigenomics, and metabolomics, novel biomarkers and therapeutic targets have been revealed in NKTCL. Whole-exome sequencing studies identify recurrent somatic gene mutations, involving RNA helicases, tumor suppresso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 66 publications
1
17
0
Order By: Relevance
“…To examine the genome diversity of EBV, complete genomes of 126 EBV strains derived from populations of different regions (Asia, n = 42; Africa, n = 35; Europe, n = 18; North America, n = 9; Oceania, n = 21; and unclassified, n = 1) and disease types (NPC, n = 27; BL, n = 19; GC, n = 16; HL, n = 8; infectious mononucleosis, IM, n = 6; posttransplant lymphoproliferative disorders, PTLD, n = 19; spontaneous lymphoid cell lines, sLCL, n = 30; and unclassified, n = 1) were collected (Table S3). Phylogenetic analysis (Figure 3A) and comparison of EBV sequence coverage/ SNVs (Peng et al, 2019) (Figure S4B) revealed similarity (higher sequence coverage/less SNVs) between EBV sequences in NKTCL and those of Asia or NPC, providing genetic evidence for geographic prevalence of NKTCL in Asian populations and common involvement of nasal/paranasal area (Xiong and Zhao, 2018). SNVs of EBV genome were also strongly associated with disease pathogenesis (Peng et al, 2019;Xu et al, 2019).…”
Section: Figure 2 Relationship Between Cell Of Origin and Molecular Subtypes In Nktclmentioning
confidence: 90%
“…To examine the genome diversity of EBV, complete genomes of 126 EBV strains derived from populations of different regions (Asia, n = 42; Africa, n = 35; Europe, n = 18; North America, n = 9; Oceania, n = 21; and unclassified, n = 1) and disease types (NPC, n = 27; BL, n = 19; GC, n = 16; HL, n = 8; infectious mononucleosis, IM, n = 6; posttransplant lymphoproliferative disorders, PTLD, n = 19; spontaneous lymphoid cell lines, sLCL, n = 30; and unclassified, n = 1) were collected (Table S3). Phylogenetic analysis (Figure 3A) and comparison of EBV sequence coverage/ SNVs (Peng et al, 2019) (Figure S4B) revealed similarity (higher sequence coverage/less SNVs) between EBV sequences in NKTCL and those of Asia or NPC, providing genetic evidence for geographic prevalence of NKTCL in Asian populations and common involvement of nasal/paranasal area (Xiong and Zhao, 2018). SNVs of EBV genome were also strongly associated with disease pathogenesis (Peng et al, 2019;Xu et al, 2019).…”
Section: Figure 2 Relationship Between Cell Of Origin and Molecular Subtypes In Nktclmentioning
confidence: 90%
“…In the present study, to decrease the bias caused by clonal hematopoiesis associated mutations, the age range of the included patients was narrow, matched ctDNA-PBMC sample was applied, and a sequencing panel was conducted according to a previous gene-expression profiling study on ENKTL. Zhao et al confirmed that the most frequently mutated genes in NKTCL were the RNA helicase gene DDX3X , tumor suppressors ( TP53 and MGA ), JAK-STAT pathway molecules ( STAT3 and STAT5b ) and epigenetic modifiers ( MLL2, ARID1A, EP300 and ASXL3 ) [ 36 , 37 ]. In addition to these recurrent mutations, JAK3, KMT2D, EZH2, NOTCH1 and TET2 were also identified by different groups [ 38 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…This has led to a better understanding of the molecular pathogenesis of this entity, the discovery of new targeted therapies, and more recently, to the proposal of a classification according to the molecular changes associated with clinical prognosis. In Table 3 , the main genetic features reported in ENKTCL so far are summarized [ 81 , 124 , 125 ].…”
Section: Enktcl Genetic Featuresmentioning
confidence: 99%